Implementation of Gender Mainstreaming Policy at the Women's Empowerment Agency in East Kutai Regency - Salasiah Salasiah; Raudah Mahmud; Marsuq Marsuq; Jamiah Jamiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The results of the research indicate that (1) the implementation of gender mainstreaming policy seen from the abolishment of Medium-Term Development Plan of East Kutai Regency prioritizes the improvement of women's capacity and role in development, especially the participation of women in the government, private sector, labor force and improvement of gender development index. While the gender mainstreaming policy contained in Women's and Family Empowerment Agency strategic plan shows that the enactment of strategies such as increasing participation of women in private institutions and government.There is a description of the activities that run optimally such as the Exhibition of Women's Works in the Field of Development in addition there are also activities that have not run optimally such as Building a Women Awakening Activity in Politics, this activity needs to be maximized again by Women's and Family Empowerment Agency. (2) The factors influencing the implementation of policies such as environmental conditions indicate that the community is still less concerned with women's participation in public decisions and public policy. Then in the inter-organizational relationship factor, the action plan of gender mainstreaming in each Unit of Regional Work Unit is implemented in harmony so that requires cooperation between the regional device work unit and cross-sectoral involvement. Furthermore, the Resource factor shows that the quantity of women in Women's and Family Empowerment Agency has more number than men. In addition, support in the form of equipment and equipment is sufficient and the characteristic factor of the implementing agency capability shows the commitment of Women's and Family Empowerment Agency employees in socializing gender responsive development.